Surface properties of sol-gel-based fluorine-containing ceramic coatings - ÇAKMAKÇI, EMRAH; KAYAMAN APOHAN, NİLHAN (SPRINGER, 2018)
In this work, sol-gel-based non-stick ceramic coating formulations were prepared and coated onto aluminum panels in order to investigate their surface properties. The effect of the addition of optimal amount of fluorine-containing silane compound (FAS) on the surface and adhesion properties were also investigated. The morphology, structure, and elemental chemical composition of the coatings were characterized by scanning electron microscopy, atomic force microscopy (AFM), energy dispersion spectrum (SEM/EDAX), Fourier-transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS), respectively. Moreover, several properties of the coatings such as cross-cut adhesion, hardness, gloss, and contact angle (CA) were determined. When fluorine was introduced, the pencil hardness was increased to 6H. Fluorinated non-stick ceramic coatings were found to have good adhesion on the aluminum substrates [GRAPHICS] Sol-gel-based non-stick ceramic coatings were prepared. Coatings were applied onto aluminum substrates and were thermally cured. Ceramic coatings exhibited good adhesion.
Keywords: Ceramic coatings; Sol-gel; Silica colloid; Hydrophobic; Adhesion; THIN-FILMS; OPTIMIZATION; COPOLYMERS; POLYMERS